EFL Teachers’ Problems in HOTS Implementation during Covid Pandemic - Amalul Umam; Movi Riana Rahmawanti; Alan Jaelani (UNIB Press, 2022)
Even though the implementation of higher-order thinking skills has been mandated by the Curriculum 2013, some English teachers find it complex, especially during the covid-19 outbreak. This study aims at finding out the problems faced by three English teachers in implementing higher-order thinking skills. It is framed under a case study design in which documentation and semi-structured interview were used for data collection. Data gathered from both semi-interviewed and documentation were analyzed using thematic analysis in which the data were coded into some themes. The finding reveals that teachers have some external and internal problems in the implementation of higher-order thinking skills. For the internal factors, the teachers admitted that they lacked training and exposure to the integration of higher-order thinking skills. They acknowledged that they frequently employ instructional strategies they have used successfully in the past. While for the external factors, the teachers asserted that the students lack the motivation to learn English online. The majority of students choose not to participate in learning activities. This study suggests that teachers must engage in continuing professional development (CPD), which can be accomplished in a variety of methods, in order to encourage the integration of higher-order thinking abilities in the classroom. If the government and the schools where the instructors educate support this CPD, it will be successful.